PERANCANGAN FURNITURE RUANG TAMU TERINSPIRASI DARI HUTAN BAMBU SUKOLILO - Salsabila Prionggo; Wyna Herdiana (Narada : Jurnal Desain dan Seni, 2020)
As the times progress, the population in Indonesia will also grow. What was followed by the increasing need for housing and land. The increasing of land for a place to live causes a limited available vacant land, therefore an alternative has emerged, namely the size of a house with a small type and vertical residence, such as apartments and flats. Even though it has a limited land area, it can still give a beautiful impression to the living room. Because living room is the main room which is used as a place to receive guests and shows the social status of the house owner. Therefore, we make furniture for the living room with a limited area, inspired by the shape and aesthetics of the bamboo forest in Sukolilo Surabaya.